A copper-based high-entropy alloy powder for blue-light laser cladding additive manufacturing and its application
Through copper-based high-entropy alloy powder and blue-ray laser cladding technology composed of specific elements, the problem of multi-component solid solution phase instability of high-entropy alloy powder is solved, and high-quality coating forming and excellent wear resistance and corrosion resistance are achieved. Performance, suitable for surface protection of marine equipment.
Patent Information
- Application Number
- CN202311814149.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-12-27
AI Technical Summary
The multi-component solid solution phase of existing high-entropy alloy powders is unstable, resulting in poor coating forming quality and unstable wear and corrosion resistance.
Copper-based high-entropy alloy powder composed of specific elements and content ranges, including 23-25% Cu, 22-24% Zn, 22-24% Mn, 22-24% Ni, 3.5-4.5% Sn, 1-2 %Si, the coating is prepared by blue laser cladding technology to form a stable BCC single-phase structure.
It achieves high-quality coating forming, free of cracks, excellent wear, corrosion and anti-fouling properties, and is suitable for surface protection and remanufacturing of key moving parts in service in extreme marine conditions.
Smart Images

Figure CN117551998B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of surface engineering technology, and in particular to a copper-based high-entropy alloy powder for blue-light laser cladding additive manufacturing and an application thereof. Background Art
[0002] In the harsh marine service environment, the key moving parts of marine equipment such as ships and offshore platforms suffer serious surface damage due to the synergistic effects of wear, corrosion, and microbial contamination, which in turn has a direct impact on the service safety and life of the equipment. Surface coating technology is an important means of surface protection for key moving parts of marine equipment, especially laser cladding surface coating technology, which has the advantages of high efficiency, high performance, strong interface metallurgical bonding, green energy saving and environmental protection, and provides an effective means for the preparation and application of surface protective coatings for key moving parts of marine equipment. Traditional coatings, thermal spraying, physical / chemical vapor deposition and other surface coating technologies are prone to failure and cannot play a protective role after long-term impact and mechanical action due to limited interface bonding strength, and cannot meet the long-term protection needs of key moving parts of marine engineering equipment. Laser cladding additive manufacturing technology has become an important technology for the preparation of wear-resistant and impact-resistant coatings due to its series of advantages such as controllable thickness, high metallurgical bonding strength and diverse materials.
[0003] Powder materials are the key foundation for the performance of laser cladding coatings, but there are currently few powders specifically designed for laser cladding coatings for extreme marine conditions. High-entropy alloys, through the design concept of high mixed entropy stable solid solution, reduce the tendency of ordering and segregation of alloy atoms, forming an alloy composed only of a simple solid solution phase. It not only has strength, hardness and corrosion resistance that exceed conventional alloys, but also maintains good plasticity and has excellent properties such as high strength, high hardness and high corrosion resistance. It is expected to become an important material for surface protection of key moving parts of marine equipment.
[0004] Chinese patent CN110230056B "Low-melting-point high-entropy alloy powder for laser surface modification of magnesium-lithium alloys, preparation method and application thereof" discloses a low-melting-point high-entropy alloy powder for laser surface modification of magnesium-lithium alloys, but the multi-component solid solution phase of the high-entropy alloy powder is unstable, resulting in poor coating forming quality and unstable wear and corrosion resistance.
[0005] Therefore, it is of great significance to develop a copper-based high-entropy alloy material and its preparation method for blue light laser cladding additive manufacturing that can effectively control the multi-component solid solution phase of high-entropy alloy powder, has good coating forming quality and excellent performance. Summary of the invention
[0006] In view of the problems of unstable multi-component solid solution phase, poor coating forming quality and unstable wear and corrosion resistance of existing high entropy alloy powder materials, the present invention provides a copper-based high entropy alloy powder for blue light laser cladding additive manufacturing and its application, which is composed of specific elements and content ranges, has excellent sphericity and fluidity, a stable two-phase structure and a stable and controllable content, a formed coating and a substrate metallurgically bonded, the coating has high forming quality, is crack-free, and has excellent wear resistance, corrosion resistance and anti-fouling properties, high preparation efficiency, and little thermal impact on the substrate, and can be used for surface protection and remanufacturing of key moving parts serving in extreme marine conditions.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A copper-based high-entropy alloy powder for blue-light laser cladding additive manufacturing comprises the following elemental components by mass percentage:
[0009] 23-25% Cu, 22-24% Zn, 22-24% Mn, 22-24% Ni, 3.5-4.5% Sn, 1-2% Si.
[0010] Furthermore, the particle size distribution range is 55-105 μm, D50 is 75-95 μm, fluidity is 15-20 s / 50 g, and sphericity is 95-100%.
[0011] Another object of the present invention is to provide a copper-based high-entropy alloy coating for blue light laser cladding additive manufacturing.
[0012] A copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing is prepared from the copper-based high-entropy alloy powder for blue-light laser cladding additive manufacturing described in any of the above items.
[0013] Furthermore, the coating has a thickness of 0.5-1.5 mm.
[0014] Another object of the present invention is to provide a method for preparing a copper-based high entropy alloy coating for blue light laser cladding additive manufacturing.
[0015] A method for preparing the above-mentioned copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing comprises the following steps:
[0016] S1. Perform induction preheating on the substrate;
[0017] S2. Depositing the copper-based high-entropy alloy powder for blue-light laser cladding additive manufacturing onto the surface of the substrate by blue-light laser cladding, thereby obtaining the copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing.
[0018] Furthermore, the induction preheating treatment in S1 is preheating at 300-400° C. for 10-20 min.
[0019] Furthermore, the process parameters of the blue light laser cladding described in S2 include: blue light laser power of 2200-2500 W, spot diameter of 1-3 mm, powder feeding rate of 1.8-2.5 kg / h, laser scanning rate of 90-100 m / min, and overlap rate of 45-65%.
[0020] Furthermore, the blue light laser cladding described in S2 is performed under the protection of an inert gas.
[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0022] (1) The copper-based high-entropy alloy powder for blue-light laser cladding additive manufacturing of the present invention is composed of specific elements and content ranges. Copper ions have excellent bactericidal effects and can kill marine organisms such as algae and barnacles on the surface of marine engineering equipment, so that the copper-based coating has excellent anti-fouling properties. A high-performance high-entropy alloy coating can be obtained by regulating the content of elements such as Cu, Zn, Mn, and Ni, but it presents a two-phase structure of FCC and BCC. Since laser cladding additive manufacturing is a non-equilibrium solidification process, the formed two-phase structure is unstable and the content is uncontrollable, which leads to unstable wear and corrosion resistance. By adding a certain amount of Sn and Si elements, the stable formation of the BCC single-phase structure of the CuZnMnNi alloy manufactured by laser cladding additive manufacturing can be effectively promoted, thereby having a thermodynamic high entropy effect, a structural lattice distortion effect, a dynamic hysteresis diffusion effect, and a performance cocktail effect, and excellent wear resistance, corrosion resistance and other properties. At the same time, there are many defects in the formation of CuZnMnNi coatings manufactured by laser cladding additive manufacturing. The Sn element has a strong deoxidation and self-melting effect, which can improve the forming quality of the laser cladding CuZnMnNi coating, reduce the impurity content of the cladding layer, and significantly improve the forming quality of the cladding layer. However, if the content of Sn and Si elements is too little, the structural stability effect and the improvement effect of forming quality are not good; if the content of Sn and Si elements is too high, they are easy to form brittle and hard inclusion phases, causing cracking of the coating and affecting the forming quality of the coating; therefore, the present invention has repeatedly studied and accurately controlled the content ratio of Cu, Zn, Mn, Ni, Sn, and Si elements, and the obtained blue-light laser cladding additive manufacturing copper-based high-entropy powder for blue-light laser cladding additive manufacturing has uniform composition, excellent sphericity and fluidity, and uniform particle size distribution. The formed BCC single-phase structure is stable, which is very suitable for the use of blue-light laser cladding additive manufacturing technology.
[0023] (2) In the present invention, the copper-based high entropy alloy coating for blue laser cladding additive manufacturing prepared by blue laser cladding technology using powders containing specific elements and content ranges can form a BCC solid solution phase with high thermal stability, which has a thermodynamic high entropy effect, a structural lattice distortion effect, a dynamic hysteresis diffusion effect, and a cocktail effect in performance, thereby having excellent wear resistance, corrosion resistance and other excellent properties. In addition, the release of copper ions on the surface of the coating can directly kill marine organisms such as algae and barnacles on the surface of marine engineering equipment, and has excellent anti-fouling performance.
[0024] (3) The copper-based high-entropy alloy coating for additive manufacturing by blue-light laser cladding of the present invention is prepared by blue-light laser cladding technology, which has high efficiency, easy operation, low cost, little thermal impact on the substrate, and forms a metallurgical bond with the substrate, thus solving the high reflection problem existing in traditional red-light laser cladding. The prepared copper-based high-entropy alloy coating for additive manufacturing by blue-light laser cladding is dense and defect-free. The obtained coating can be used for surface protection and remanufacturing of key moving parts serving in extreme marine conditions, and has important economic value and promotion significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0026] Figure 1 This is an electron microscope image of the copper-based high-entropy alloy powder used for blue light laser cladding additive manufacturing in Example 1 of the present application.
[0027] Figure 2 This is the X-ray diffraction pattern of the copper-based high-entropy alloy coating for blue light laser cladding additive manufacturing in Example 1 of the present application. DETAILED DESCRIPTION
[0028] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.
[0029] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0030] Example 1
[0031] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing comprises the following steps:
[0032] S1. The substrate is subjected to induction preheating treatment at 350°C for 15 min;
[0033] S2. A copper-based high-entropy alloy powder for blue light laser cladding additive manufacturing containing 24% Cu, 24% Zn, 24% Mn, 23% Ni, 3.8% Sn and 1.2% Si is deposited on the surface of a substrate by blue light laser cladding. The copper-based high-entropy alloy powder for blue light laser cladding additive manufacturing has a particle size distribution range of 55-105μm, D50 of 80μm, fluidity of 17s / 50g, and sphericity of 95%. The process parameters of the blue light laser cladding additive manufacturing include: a blue light laser power of 2300W, a spot diameter of 2mm, a powder feeding rate of 2kg / h, a laser scanning rate of 95m / min, an overlap rate of 55%, and inert gas protection is performed during the blue light laser cladding process to obtain the copper-based high-entropy alloy coating for blue light laser cladding additive manufacturing, and the coating thickness is 1mm.
[0034] Example 2
[0035] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0036] Compared with Example 1, the copper-based high entropy alloy powder for blue light laser cladding additive manufacturing contains 23% Cu, 23% Zn, 24% Mn, 23.8% Ni, 4.2% Sn and 2% Si.
[0037] Example 3
[0038] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0039] Compared with Example 1, the copper-based high entropy alloy powder for blue light laser cladding additive manufacturing contains 25% Cu, 24% Zn, 24% Mn, 22.2% Ni, 3.8% Sn and 1% Si.
[0040] Example 4
[0041] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0042] Compared with Example 1, the laser power of S1 blue light laser cladding is 2500W.
[0043] Example 5
[0044] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0045] Compared with Example 1, the scanning speed of S1 blue light laser cladding is 100 m / min.
[0046] Comparative Example 1
[0047] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0048] Compared with Example 1, the copper-based high-entropy alloy powder for blue light laser cladding additive manufacturing in this comparative example contains 23% Cu, 24% Zn, 24% Mn, 23% Ni, 4.8% Sn and 1.2% Si, that is, the Sn element is excessive.
[0049] Comparative Example 2
[0050] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0051] Compared with Example 1, the copper-based high-entropy alloy powder for blue light laser cladding additive manufacturing in this comparative example contains 25% Cu, 25% Zn, 25% Mn, 24% Ni, 0% Sn and 1% Si, that is, does not contain Sn element.
[0052] Comparative Example 3
[0053] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0054] Compared with Example 1, the copper-based high-entropy alloy powder for blue light laser cladding additive manufacturing in this comparative example contains 25% Cu, 25% Zn, 25% Mn, 24% Ni, 1% Sn and 0% Si, that is, does not contain Si element.
[0055] Comparative Example 4
[0056] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0057] Compared with Example 1, the sphericity of the copper-based high entropy alloy powder for blue light laser cladding additive manufacturing in this comparative example is 80%.
[0058] Comparative Example 5
[0059] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0060] Compared with Example 1, the D50 of the copper-based high-entropy alloy powder for blue light laser cladding additive manufacturing in this comparative example is 65 μm.
[0061] Comparative Example 6
[0062] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0063] Compared with Example 1, the D50 of the copper-based high-entropy alloy powder for blue light laser cladding additive manufacturing in this comparative example is 110 μm.
[0064] Comparative Example 7
[0065] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0066] Compared with Example 1, the fluidity of the copper-based high-entropy alloy powder for blue light laser cladding additive manufacturing in this comparative example is 30s / 50g.
[0067] Comparative Example 8
[0068] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0069] Compared with Example 1, step S2 of this comparative example uses a red light laser cladding method to deposit the copper-based high entropy alloy powder for blue light laser cladding additive manufacturing on the surface of the substrate.
[0070] Comparative Example 9
[0071] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0072] Compared with Example 1, the blue light laser cladding process parameters in step S2 of this comparative example are: laser power 2000W.
[0073] Comparative Example 10
[0074] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0075] Compared with Example 1, the blue light laser cladding process parameters in step S2 of this comparative example are: laser power 3000W.
[0076] Comparative Example 11
[0077] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0078] Compared with Example 1, the blue light laser cladding process parameters in step S2 of this comparative example are: scanning speed 80 m / min.
[0079] Comparative Example 12
[0080] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0081] Compared with Example 1, the blue light laser cladding process parameters in step S2 of this comparative example are: scanning speed 120 m / min.
[0082] Comparative Example 13
[0083] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0084] Compared with Example 1, step S1 of this comparative example does not perform induction preheating treatment.
[0085] Comparative Example 14
[0086] A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, wherein the steps not specifically described are the same as those in Example 1, except that:
[0087] Compared with Example 1, in the blue light laser cladding process in step S2 of this comparative example, no inert atmosphere protection is performed.
[0088] Figure 2 This is the XRD test result of the copper-based amorphous coating for ultra-high-speed blue laser cladding additive manufacturing of Example 1 of the present application. It can be observed that the coating forms a stable BCC solid solution phase. The characterization test results of the remaining examples are basically consistent with those of Example 1.
[0089] The above samples were subjected to performance tests, and the experimental test methods were as follows:
[0090] Test method for coating forming quality: Determined in accordance with the national standard "GB / T 36591-2018"
[0091] Test method for wear weight loss: Determined in accordance with the national standard "GB / T 12444-2006"
[0092] Corrosion rate test method: Determined in accordance with the national standard "GB / T 40299-2021"
[0093] Microhardness test method: Determined in accordance with the national standard "GB / T 4342-1991"
[0094] Anti-biological fouling test method: refer to the national standard "GB / T5370-2007" test
[0095] Among them, the microhardness indicates the hardness of the coating, and the larger the value, the higher the hardness of the coating; the wear loss weight indicates the wear resistance of the coating, and the smaller the value, the better the wear resistance of the coating; the corrosion rate indicates the corrosion resistance of the coating, and the smaller the value, the better the corrosion resistance of the coating; the fouling wet weight indicates the anti-fouling performance of the coating, and the smaller the value, the better the anti-fouling performance of the coating.
[0096] The test results of Examples 1-5 and Comparative Examples 1-14 are shown in the following table:
[0097] Table 1 Test results of 1-5 and comparative examples 1-14
[0098]
[0099]
[0100] It can be seen from Table 1 that the coatings in the embodiments of the present invention have good forming quality and no defects, the weight loss from abrasion is less than 49 mg, and the lowest corrosion rate can reach 0.06 mm·a. -1 , the wet weight of the pollution is 700g·m -2 It has outstanding comprehensive performance compared with the comparative examples, indicating that the copper-based high-entropy alloy coating for blue light laser cladding additive manufacturing of the present invention has excellent corrosion resistance, abrasion resistance and anti-fouling properties.
[0101] However, due to the excessive Sn element, the forming quality of comparative example 1 is poor, the microhardness is low, the wear loss reaches 100 mg, and the antifouling performance is poor; due to the excessive Sn and Si elements, the wear loss of comparative examples 2 and 3 is large, and the wear resistance is poor, especially the wet weight of the fouling of comparative example 3 reaches 1798 g·m -2 , poor antifouling performance; Comparative Examples 4, 5, 6, and 7 changed the powder sphericity, D50, and fluidity, resulting in poor coating forming quality, many defects, high corrosion rate, and the wet weight of fouling was higher than 1600 g·m -2 Comparative Example 8 uses red light laser cladding, and the overall performance of the coating obtained is the worst among all the embodiments and comparative examples, with low microhardness, abrasion weight loss of up to 143 mg, and fouling wet weight of up to 1795 g·m -2; Comparative Examples 9, 10, 11, and 12 changed the ultra-high-speed blue-light laser cladding process parameters, and the corrosion resistance, abrasion resistance, and anti-fouling performance were all poor; Comparative Example 13 did not perform induction preheating treatment, and Comparative Example 14 did not perform inert atmosphere protection. The comprehensive performance was acceptable in each comparative example, but was far from being comparable to that of each embodiment. It is illustrated that the copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing obtained by the specific ultra-high-speed blue-light laser cladding of the copper-based high-entropy alloy powder for blue-light laser cladding additive manufacturing composed of specific elements and content ranges of the present invention has significantly excellent comprehensive performance.
[0102] In summary, the copper-based high-entropy alloy powder for blue-light laser cladding additive manufacturing of the present invention is composed of specific elements and content ranges, and the content ratio of Cu, Zr, Ti, Ni, Sn and Si elements is precisely regulated. The obtained copper-based high-entropy alloy powder for blue-light laser cladding additive manufacturing has uniform composition, excellent sphericity and fluidity, and uniform particle size distribution. The formed BCC solid solution phase structure is stable and controllable, has excellent bactericidal effect, high strength, high hardness, high corrosion resistance, and high coating forming quality; the blue-light laser cladding blue-light laser cladding additive manufacturing copper-based high-entropy alloy powder prepared by the powder using the blue-light laser cladding technology The copper-based high-entropy alloy coating with a stable BCC single-phase structure has high entropy effect in thermodynamics, lattice distortion effect in structure, hysteresis diffusion effect in dynamics and cocktail effect in performance, and has excellent properties such as wear resistance and corrosion resistance. The specific short-wavelength blue light laser cladding is used to greatly improve the absorption rate of copper alloy to laser energy, and solves the high reflection problem of traditional red light laser cladding. The prepared copper-based high-entropy alloy coating for blue light laser cladding additive manufacturing is dense and defect-free. The obtained coating can be used for surface protection and remanufacturing of key moving parts serving in extreme marine conditions, which has important economic value and promotion significance.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, characterized in that: The following steps are involved: S1. Perform induction preheating on the substrate; S2. depositing the copper-based high entropy alloy powder for blue laser cladding additive manufacturing onto the surface of the substrate by blue laser cladding, thereby obtaining the copper-based high entropy alloy coating for blue laser cladding additive manufacturing; S2 The process parameters of the blue laser cladding include: blue laser power of 2200-2500W, spot diameter of 1-3mm, powder feeding rate of 1.8-2.5kg / h, laser scanning rate of 90-100m / min, and overlap rate of 45-65%; S2: The blue light laser cladding is carried out under the protection of an inert gas; The copper-based high-entropy alloy powder for blue-light laser cladding additive manufacturing comprises the following elemental components by mass percentage: 23-25% Cu, 22-24% Zn, 22-24% Mn, 22-24% Ni, 3.5-4.5% Sn, 1-2% Si, particle size distribution range is 55-105μm, D50 is 75-95μm, fluidity is 15-20s / 50g, and sphericity is 95-100%.
2. A method for preparing a copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing according to claim 1, characterized in that: The induction preheating treatment in S1 is preheating at 300-400°C for 10-20 minutes.
3. A copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing, characterized in that: The coating is prepared by the preparation method of the copper-based high-entropy alloy coating for blue light laser cladding additive manufacturing as described in any of the above items.
4. A copper-based high-entropy alloy coating for blue-light laser cladding additive manufacturing according to claim 3, characterized in that: The thickness of the coating is 0.5-1.5 mm.
Citation Information
Patent Citations
Low-melting-point high-entropy alloy powder for laser surface modification of magnesium-lithium alloys, its preparation method and application
CN110230056B
High strength and toughness wear-resistant high entropy copper alloy
CN109338202A
High-entropy alloy material and preparation method thereof
CN111926232A
Metal alloys including copper
US20170349975A1